IMPLEMENTATION OF TAUGHID EDUCATION IN EARsLY CHILDHOOD - Ina Winarsih; Puji Yulianty; Heru Wardany (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
Tawhid education in early childhood is a crucial foundation for developing children's faith, morals, and personality from an early age. This study aims to identify strategies for implementing Tawhid education in early childhood. The research method used was qualitative with a descriptive approach. Data were obtained through interviews, observations, and documentation involving teachers, parents, and early childhood education institutions. Participants were selected purposively to ensure relevance to the research focus. Data were analyzed using thematic analysis techniques to identify patterns and strategies for implementing Tawhid education. The results indicate that Tawhid education is implemented through the practice of worship, role models from parents and teachers, curriculum integration in early childhood education (PAUD), and community support. The discussion emphasizes the importance of collaboration between families, schools, and the community, as well as the need for innovation through the use of digital media. The conclusion suggests that Tawhid education can be effectively instilled from an early age, but further research is needed to evaluate the effectiveness of technology-based methods.